Pelatihan Penggunaan Digital Marketing (E-Commerce) Untuk UMKM Jamur Tiram Berbasis Digital Di Desa Kelindang Atas Kecamatan Merigi Kelindang Kabupaten Bengkulu Tengah - Gustini, Gustini; Azuwandri, Azuwandri; Susanto, Yohanes; Putri, Sudriyanti; Faridah, Faridah (STIA Bengkulu, 2024)
This community service was carried out in Kelindang Atas Village, Merigi Kelindang District, Central Bengkulu Regency with the theme of Training on the Use of Digital Marketing (E-Commerce) for Digital-Based Oyster Mushroom MSMEs in Kelindang Atas Village, Merigi Kelindang District, Central Bengkulu Regency, where this training method was carried out using workshop on the use of digital marketing (E-Commerce), how to open a shop in an online store and how to do digital branding. The aim is for MSME players in Kelindang Atas Village, Merigi Kelindang District, Central Bengkulu Regency to gain additional insight into digital marketing concepts and technological products used for product marketing, provide training and simulations about the use of digital media in product marketing, compose effective persuasive messages which is interesting and provides solutions or problem solving to enable MSME players to promote products through digital media, so that people know how to use digital marketing (E-Commerce) properly and correctly and on target. So, it is able to increase the income of MSME players and can market products better by combining marketing both conventionally and online.